Fauna diversity, production potential and total economic value of mangrove ecosystems in Mentawir Village, East Kalimantan, Indonesia - Rochadi Kristiningrum; Abubakar M. Lahjie; MASJAYA; SYAHRIR YUSUF; YOSEP RUSLIM; AMIR MA’RUF (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Kristiningrum R, Lahjie AM, Masjaya, Yusuf S, Ruslim Y, Ma’ruf A. 2020. Fauna diversity, production potential and total economic value of mangrove ecosystems in Mentawir Village, East Kalimantan, Indonesia. Biodiversitas 21: 1940-1953. Mangroves play important role in life. The benefits of the mangrove ecosystem consist of ecological and socio-economic values. However, it is a challenge to discern how the mangrove ecosystem provides a comprehensive economic value. This research is aimed to analyze the Total Economic Value (TEV) of mangrove ecosystems in Mentawir Village, North Penajam Paser District, East Kalimantan Province. This aim will be achieved by conducting fauna inventory, analysis of mangrove wood production potential, social-economic interviews, and infrastructure cost analysis as the inputs to calculate four elements (i.e. Direct Use Value, Indirect Use Value, Option Value, and Existence Value) to sum up the TEV. The research used a mixed-method combining both qualitative and quantitative methods. Fauna inventory was conducted using boat survey method and interviews with local fishermen. Data on mangrove wood production was obtained using the systematic random sampling method by establishing two plots with an area of one hectare for each plot to calculate mean annual increment (MAI) and current annual increment (CAI). The economic value of the mangrove ecosystem was calculated using market price values, replacement costs, and the Contingent Valuation Method (CVM). The results of fauna inventory consisted of 3 species of mammals, 1 species of reptile, 16 species of birds, 25 types of fish, 8 species of crustaceans, and 7 species of mollusks. The economic valuation resulted in the contribution of direct use value with 39.56% in the form of wood (94,875,000,000 IDR) and fishery products (103,500,000,000 IDR); indirect use value with 53.47% in the form of breakwater (38,028,881,407 IDR), abrasion resistance (218,549,528,110 IDR), and carbon sequestration (11,580,313,067); option value with 6.92% in the form of biodiversity (34,690,085,038 IDR); and existence value with 0.05% (241,500,000 IDR). All these resulted in the total economic value (TEV) of the mangrove ecosystem in Mentawir Village of 501,465,307,621 IDR. Therefore, this value can be the basis for policymakers in managing natural resources so that the ecosystem is more protected and sustainable, and can continue to provide environmental services for the welfare of the community.